2008
DOI: 10.1158/1078-0432.ccr-07-4953
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of BRCA2-Deficient Mammary Tumor Cell Growth by AZD2281 and Cisplatin

Abstract: Purpose: To assess efficacy of the novel, selective poly(ADP-ribose) polymerase-1 (PARP-1) inhibitor AZD2281against newly established BRCA2-deficient mouse mammary tumor cell lines and to determine potential synergy between AZD2281and cisplatin. Experimental Design: We established and thoroughly characterized a panel of clonal cell lines from independent BRCA2-deficient mouse mammary tumors and BRCA2-proficient control tumors. Subsequently, we assessed sensitivity of these lines to conventional cytotoxic drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
223
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(234 citation statements)
references
References 44 publications
9
223
1
1
Order By: Relevance
“…This radiosensitization may result from PARP-mediated Targeting DDR pathways to improve cancer treatment F Al-Ejeh et al inhibition of single-strand break repair at stalled replication forks leading to the creation of DSBs (Haince et al, 2005). Consequently, up to 1000-fold higher sensitivity of BRCA-deficient (Bryant et al, 2005;Farmer et al, 2005;McCabe et al, 2005McCabe et al, , 2006Evers et al, 2008) or FA protein-deficient cells to PARP inhibition seems to depend on the excess of DSBs generated in the presence of compromised HR. Increased G2/M arrest upon PARP inhibition could explain the higher growth inhibition in FA proteindeficient cells .…”
Section: Arrest/senescencementioning
confidence: 99%
“…This radiosensitization may result from PARP-mediated Targeting DDR pathways to improve cancer treatment F Al-Ejeh et al inhibition of single-strand break repair at stalled replication forks leading to the creation of DSBs (Haince et al, 2005). Consequently, up to 1000-fold higher sensitivity of BRCA-deficient (Bryant et al, 2005;Farmer et al, 2005;McCabe et al, 2005McCabe et al, , 2006Evers et al, 2008) or FA protein-deficient cells to PARP inhibition seems to depend on the excess of DSBs generated in the presence of compromised HR. Increased G2/M arrest upon PARP inhibition could explain the higher growth inhibition in FA proteindeficient cells .…”
Section: Arrest/senescencementioning
confidence: 99%
“…1 PARP inhibitors also impair, via other mechanisms, high fidelity repair of double-strand DNA breaks in tumor cells with deficiencies in homologous recombination repair (HRR), such as BRCA1/2 mutations (BRCA1/2m). 2,3 Impaired DNA repair in tumor cells with HRR deficiencies leads to irreparable double-strand breaks being formed that result in tumor cell death by synthetic lethality. 4 PARP inhibitors can also induce lethality in tumor cells that have deficiencies in DNA damage repair mechanisms other than HRR deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies then demonstrated that treatment with a PARP inhibitor had a significant impact on orthotopic transplants of BRCAnull breast cancers transplanted from conditional mutant mice. [21][22][23] Taken together, these studies have provided the preclinical rationale for exploring PARP inhibition as a strategy to treat malignancies in which the cells are deficient in HR-directed repair. The concept of using PARP inhibitors as single agents to induce cell death through synthetic lethality represents a novel approach to cancer treatment but may not be the only mechanism by which PARP inhibitors could improve cancer therapy.…”
Section: Rationale For Parp Inhibition In Brca-associated Cancermentioning
confidence: 99%
“…36 Preclinical studies of combination therapy with PARP inhibitors and platinum agents animal models of BRCAdeficient breast cancers have shown enhanced efficacy (and toxicity). 21,37 The lack of HRdirected repair capability leads to cell death after exposure to the aggregate insult of doublestrand breaks resulting from the inability to repair platinum-induced crosslinks and similar breaks resulting from replication fork collapse at the site of SSB that are not repaired due to PARP inhibition.If there is a defect in HR-directed repair in subsets of TNBC, one would expect exquisite platinum sensitivity in that setting as well. Clinical studies examining this hypothesis are not conclusive, perhaps in part due to the heterogeneity of TNBC and the design of the available studies.…”
mentioning
confidence: 99%